RUSSIAN ENERGODIPLOMACY IN THE BALKANS: PURPOSES, FACTORS, AND OBSTACLES - Baranov, Andrey (Srpska politička misao, 2025)
The study’s subject is the Russian Federation’s energy diplomacy in Turkey and the Balkans. The article aims to identify the goals, factors, and obstacles to implementing the Russian energy diplomacy in Turkey and the Balkans. Theoretical and methodological approach of the research: the paradigm of neorealism in international relations, system approach, comparative analysis. Results and conclusions of the paper: The author clarified the importance of the Turkish and Balkan direction in Russian geopolitics and energy diplomacy, noting the Bosphorus and the Dardanelles’ key role in Russian security and foreign economic relations. Turkey is now Russia’s most important partner and stakeholder in the Balkan transport and energy highways. Anti-Russian sanctions have led to Serbia’s enclave location in the Balkan energy diplomacy system, exacerbating the competition of world powers and transnational structures for raw materials and the territory of Serbia.